(untitled) (Journal of the Asiatic Society of Bangladesh, Science, 2017)
An in vitro study was conducted to assess the effects of slums on ecosystem services particularly soil, plant and water. The research findings indicated that, samples of soil, plant and water were contaminated with heavy metals, many of which were above permissible limits. The heavy metals exceeding the permissible limits pose serious threats to the surrounding plant and animal lives. Hence, there is a health risk associated with the consumption of the vegetables grown in the slums due to the fact that the heavy metals can bio-accumulate into human body through the food chain. Asiat. Soc. Bangladesh, Sci. 43(1): 71-81, June 2017